Sweepstakes reproductive success is absent in a New Zealand snapper (Chrysophrus auratus) population protected from fishing despite "tiny" Ne/N ratios elsewhere. Issue 12 (29th June 2019) - Jones, Andrew T.; Lavery, Shane D.; Le Port, Agnès; Wang, You‐Gan; Blower, Dean; Ovenden, Jennifer
Abstract: A landmark study published in 2002 estimated a very small N e / N ratio (around 10 –5 ) in a population of pink snapper ( Chrysophrys auratus, Forster, 1801) in the Hauraki Gulf in New Zealand. It epitomized the tiny N e / N ratios (<10 –3 ) reported in marine species due to the hypothesized operation of sweepstakes reproductive success (SRS). Here we re‐evaluate the occurrence of SRS in marine species and the potential effect of fishing on the N e / N ratio by studying the same species in the same region, but in a population that has been protected from fishing since 1975. We combine empirical, simulation and model‐based approaches to estimate N e (and N b ) from genotypes of 1, 044 adult fish and estimate N using recapture‐probabilities. The estimated N e / N ratio was much larger (0.33, SE : 0.14) than expected. The magnitude of estimates of population‐wide variance in individual lifetime reproductive success (10–18) suggested that the sweepstakes effect was negligible in the study population. After evaluating factors that could explain the contrast between studies – experimental design, life history differences, environmental effects and the influence of exploitation on the N e / N ratio – we conclude that the low N e of the Hauraki Gulf population is associated with demographic instability in the harvested compared to the protected population despite circumstantial evidence that the 2002 study may have underestimated N e . This study has broad implications for the prevailing view that reproductive success in the sea is largely driven by chance, and for genetic monitoring of populations using the N e / N ratio and N b .